2002
DOI: 10.1046/j.1365-3040.2002.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of root respiration in two species of Plantago that differ in relative growth rate: the effect of short‐ and long‐term changes in temperature

Abstract: This study investigates the effect of short-and long-term changes in temperature on the regulation of root respiratory O 2 uptake by substrate supply, adenylate restriction and/or the capacity of the respiratory system. The species investigated were the lowland Plantago lanceolata L. and alpine Plantago euryphylla Briggs , Carolin & Pulley, which are inherently fast-and slow-growing, respectively. The plants were grown hydroponically in a controlled environment (constant 23 ∞ ∞ ∞ ∞ C). The effect of long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 46 publications
3
101
5
Order By: Relevance
“…At high temperature, 82% of the total CO 2 released was from respiration. The response of plant respiration to temperature is known to be acclimative, with acclimation occurring within 1 to 2 d of growth at the elevated temperature (Covey-Crump et al, 2002). Acclimation is not apparent after 6 d of growth of the cell suspension culture, which is consistent with acclimation involving tissue-level morphological and cellular changes (Armstrong et al, 2006) that are unlikely to be replicated in a cell culture.…”
Section: Increased Growth Temperature Leads To a Considerable Decreasmentioning
confidence: 59%
“…At high temperature, 82% of the total CO 2 released was from respiration. The response of plant respiration to temperature is known to be acclimative, with acclimation occurring within 1 to 2 d of growth at the elevated temperature (Covey-Crump et al, 2002). Acclimation is not apparent after 6 d of growth of the cell suspension culture, which is consistent with acclimation involving tissue-level morphological and cellular changes (Armstrong et al, 2006) that are unlikely to be replicated in a cell culture.…”
Section: Increased Growth Temperature Leads To a Considerable Decreasmentioning
confidence: 59%
“…1, where exposure of a warm-grown plant to the cold for several days results in an increase in the rate of R at a common measurement temperature (Rook 1969;Chabot and Billings 1972;Pisek et al 1973;Larigauderie and Körner 1995;Körner 1999;Atkin et al 2000b;Covey-Crump et al 2002;Zha et al 2002Zha et al , 2005Bolstad et al 2003). Conversely, exposure to high temperatures results in a decrease in the rate of R at a common temperature (Fig.…”
Section: Overviewmentioning
confidence: 97%
“…In contrast, measurements of R in roots are made using whole root systems (e.g. Smakman and Hofstra 1982;Bouma et al 1997;Covey-Crump et al 2002;Loveys et al 2003) or root segments of differing age or function (e.g. Higgins and Spomer 1976;Crawford and Palin 1981;Sowell and Spomer 1986;Weger and Guy 1991;Zogg et al 1996;Pregitzer et al 1997Pregitzer et al , 1998Burton et al 2002;Comas and Eissenstat 2004).…”
Section: Leaves V Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kattge and Knorr (2007) further derived a general formulation for quantifying the temperature acclimation effect in the parameters established by Farquhar photosynthesis models. Apart from photosynthesis, studies on the response of plant respiration to temperature have shown that increasing temperature may cause a decline of the Q10, the rate of change in respiration due to a 108C increase in temperature, leading to lower plant respirations (Wager, 1941;Atkin et al, 2000a;Atkin et al, 2000b;Tjoelker et al, 2001;Covey-Crump et al, 2002;Loveys et al, 2003). This refers to Type I acclimation as proposed by Atkin and Tjoelker (2003) and Atkin et al (2005).…”
Section: Introductionmentioning
confidence: 99%